(untitled) (The Review of Diabetic Studies, 2025)
Cardiopulmonary resuscitation (CPR) administered by paramedics is a critical life-saving intervention that significantly influences survival outcomes in emergency situations, particularly during out-of-hospital cardiac arrest (OHCA). This comprehensive review evaluates the impact of paramedic-performed CPR on patient survival rates, neurological outcomes, and overall emergency medical service (EMS) system effectiveness. The study synthesizes findings from peer-reviewed literature published between 2016 and 2025, examining key factors such as response time, quality of chest compressions, adherence to resuscitation protocols, use of adjunctive technologies (e.g., automated CPR devices, real-time feedback systems), and integration with the chain of survival. Evidence indicates that paramedic-initiated CPR markedly improves return of spontaneous circulation (ROSC) and increases the likelihood of survival to hospital discharge, especially when delivered within the first few minutes of cardiac arrest. Advanced training, continuous performance assessment, and the incorporation of decision-support technologies further enhance resuscitation outcomes. However, challenges such as fatigue, human error, and environmental constraints may affect CPR quality. This review highlights the importance of standardized training, protocol optimization, and system-level support to maximize the effectiveness of paramedic-led CPR. The findings underscore the vital role of paramedics in improving emergency response outcomes and stress the need for continuous improvement in prehospital resuscitation strategies.